Effects of the Season on the Rooting Performance on the Local Olive Types of Northern Cyprus - Nihat Yılmaz; Tijen Mahmutoğlu; Duran Özkök (Turkish Journal of Agriculture: Food Science and Technology)
In this study, rooting performance of cuttings of local olive types of Northern Cyprus taken in spring and autumn seasons was investigated. Gemlik Olive cultivar was used as the control group and 14 different local olive types constituted the experimental groups. Green cuttings taken from local olive types were initially treated with 4000 ppm indole-3-butyric (IBA) and they were then rooted in perlite medium under fogging unit in a plastic greenhouse. Following 100-days of rooting, rooting ratios, root lengths, number of roots and shooting ratios were determined. As expected, the best rooting ratio was obtained from Gemlik Olive cultivar (control group). Among the local types, the best rooting ratio (58.67%) was obtained from Çamlıköy with Type 8 olive type and the best rooting performance (45.87%) was achieved in cuttings rooted in autumn season.